Oral Ellis-Van Creveld Syndrome: A Brief Review of Literature and A Case Report - Nazemisalman, Bahareh; Salah, Shilan; Vahabi, Surena; Nabtieh, Atieh (Journal of Dentistry And Oral Implants, 2016)
EVC syndrome is a rare autosomal recessive genetic syndrome which its exact prevalence is unknown. The main manifestations of EVC include condro-ectodermal dysplasia, polydactyly, congenital heart defects and tooth and nail hypoplasia, and the survival rate of patients depends on the heart disease. EVC should be differentiated from other chondrodystrophia such as Achondroplasia and Jeune syndrome. Few cases of this syndrome have been reported in dental literature. This article is a brief review about the main orofacial features of EVC and reported all Prosthodontics and Restorative treatment of a 7-year-old girl that was born in prone family to EVC and presenting typical features of this syndrome.
Keywords: Ellis-Van Creveld syndrome; Oral manifestations; Dental considerations.